PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI METODE TTW MEDIA GAMBAR PADA PESERTA DIDIK KELAS VII - Dewi, Desyarini Puspita; Yuniani, Nila (BAPPEDA Kota Pekalongan, 2020)
The research was motivated by the low interest and value of students in writing descriptive texts in class VII students of SMP N 1 Talun. For this reason, it is n ecessary to apply learning innovations to improve student achievement. In this study, the think talk write method was applied with the help of image media in the description of text learning materials in the 2013 curriculum. , and the second cycle 76.14 increased 18.56% sufficient in the second cycle because the number of students who have completed has reached 81%. This proves that the application of the think talk write method with the help of pictorial media in learning to write descriptive texts in class VII C SMP N 1 Talun has increased and is effective. The results of observation data in the form of student activities, it was found that in learning there was good communication, in this case there was an interaction between students and teachers and bet ween students. Based on these results it can be concluded that learning to write descriptive texts using the think talk write method with the help of pictorial media has a significant increase in both the learning process, the average score of writing skills, and changes in student behavior. Class VII C students of SMP N 1 Talun after participating in learning to write descriptive text using the think -talk method, writing using pictures as media. Keywords: Improved skill writing text description, Think talk write method, Image media